Breast cancer metastasis to the stomach mimicking early gastric cancer - Kosuke Tanaka; Yohei Yabuuchi; Daisuke Yamashita; Tetsuro Inokuma (JGH Open, 2023)
Abstract A 79‐year‐old woman with a history of invasive lobular breast cancer presented with a lesion that was endoscopically and histopathologically consistent with poorly differentiated early gastric adenocarcinoma. Endoscopic submucosal dissection was performed, and histopathological examination using additional immunohistochemistry determined that the lesion was metastatic breast cancer. Even if a lesion suspicious of gastric cancer is found on endoscopy in a patient with a history of breast cancer, the possibility of metastasis should be considered and clinicians should inform the pathologists of the possibility.